The «visual common sense» on the mercosur and the left from the political humor - Campo Quintero, Willian Jesús (Oficios Terrestres, 2015)
The article analyzes the diplomatic conflict between Paraguay and the Mercosur, raised in 2012, seen from the political humor of the diary ABC Color. Four cartoons were selected that reflect continuities in the «construction of meaning» and in ites stylistic lines, corresponding to May and June, 2013, and to February, 2014. Is observed that humor strengthens the institutional position of ABC Color about the diplomatic conflict, using the hostile and tendentious joke, stereotypical, recurrent and systematical; also serves the purpose of positioning a «visual sense» regarding the representatives of the political left and relations of Paraguay with mercosur at the political and ideological levels